Evaluation of Pericarp and Seed Extract of Zizyphus rugosa Lam. for Cytotoxic Activity - KS, Vinayaka (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Ziziphus rugosa Lam. belongs to the family Rhamnaceae. It is commonly called as suran in Hindi, chunu koli in Urdu and Badara in Sanskrit and in local language is called as belamarluhanu. In the present study, we have investigated the cytotoxic potential of different concentrations (10-1000 Âµg/ml) pericarp and seed extract of Z. rugosa in terms of lethal effect on the brine shrimp Artemia nauplii. The degree of lethality was found to be directly proportional to the concentration of the extract. Seed extract showed potent cytotoxicity (LC50 of 564.73Î¼g/ml) and thus the seed extract is toxic. Highest mortality by pericarp extract was only 22% at 1000Âµg/ml concentration and thus is non-toxic. The extracts have shown bioactivity in terms of causing mortality of brine shrimps and is an addition to the scientific literature on the plant. The cytotoxic activity could be due to the phytoconstituents present in the extracts.